The pollen morphology of Pelargonium endlicherianum and Pelargonium quercetorum (Geraniaceae) in Turkey - Baser, Birol; Firat, Mehmet; Aziret, Akin (Pensoft Publ, 2016)
The pollen morphology of Pelargonium endlicherianum Fenzl. and Pelargonium quercetorum Agnew. from the family Geraniaceae was examined under light microscopy and scanning electron microscopy. Pollen morphologies are eurypalynous. The pollen grains were tricolporate, prolate-spheroidal and large. Aperture was ectoaperture, colpus was short, and the pores were oblate-spheroidal and large. The exine ornamentations were striate-reticulate and the reticula were heterobrachate. The 2 species are invasive exotics in Turkey.
Keywords: Morphology; Pelargonium; Pollen; Turkey